“Are You Really Gay Prof?”: The Transgressive Self as a Pedagogical Tool - Brown, Anthony (Social and Health Sciences, 2025)
Notwithstanding progressive constitutional protections, LGBTQ+ identities persist in being marginalised and stigmatised within numerous South African educational contexts. This occurs particularly in teacher education programmes where heteronormative and cisnormative assumptions frequently remain unchallenged. In this article, I examine the potentialities and constraints of transgressive embodiment as a pedagogical instrument for disrupting these oppressive norms and cultivating more inclusive learning environments. Drawing on theoretical insights from queer theory, critical pedagogy and postcolonial studies, I present my experiences of teaching while being visibly and unapologetically queer. These narratives are analysed through a critical, intersectional framework that considers the ways in which gender, sexuality, race and other axes of identity and power shape the pedagogical encounter. My experiences indicate that transgressive embodiment can serve as a potent tool for challenging heteronormative and cisnormative assumptions in the classroom, thereby creating space for alternative ways of knowing and being. By situating these experiences within global discourses on queer pedagogy, this article contributes to international conversations about the transformative potential of embodied resistance in diverse educational contexts. These experiences also underscore the risks and limitations of this approach. These include the emotional and professional toll of hypervisibility, the potential for student resistance and misunderstanding, and the necessity for institutional and systemic change alongside individual acts of resistance. Autoethnographic reflections such as these can contribute to a more nuanced and situated understanding of the complexities of queer pedagogies, while also indicating potential avenues for further research and praxis.